PENGARUH DESAIN PRODUK, BRAND IMAGE, HARGA DAN CELEBRITY ENDORSER TERHADAP PERILAKU SETELAH PEMBELIAN PRODUK DISTRO 3SECOND DI JEMBER - Ika Barokah Suryaningsih (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
The development of the fashion world continues to follow the existing trends and give birth to new works to meet the needs and desires of consumers so that boutiques, distributions, and so forth. In Indonesia there are several local distros that are famous and popular among young people, one of them is the 3Second distro. This study is to determine the effect of product design, brand image, price and celebrity endorser on behavior after purchasing 3Second distributions in Jember. The population of all consumers is 3Second Jember distro. the sample used was 110 respondents. The method used was purposive sampling. This type of research is explanatory research. The analytical tool used is multiple linear regression analysis. The results of the study show that product design, brand image and price significantly influence post-purchase behavior. while celebrity endorsers do not affect behavior after purchase. This research is expected to provide additional information and can be used as a material for consideration of distributions regarding factors that influence behavior after purchase.